POTENTIOMETRIC DETERMINATIONS OF DISSOCIATION CONSTANTS AND THERMODYNAMIC PARAMETERS OF 4-AMINOQUINOLINE IN AQUEOUS, AQUEOus-DIOXANE, AQUEOUS ETOH ANDAQUEOUs-MEOH SOLUTIONS AT VARIOUS TEMPERATURES (Biological Sciences - PJSIR, 2001)
The dissociation constant (pK) and thermodynamic parameters Gibb's free energies of 4-aminoquinoline are measured by potentiometric pH titrations in aqueous solution at 25 to 50°C and in three mixed aqua-organic media (dioxane, EtOH and MeOH) at 25°C ± O.loC. It is observed that pKaM and pKaT(concentration ionization and thermodynamic ionization constants) values of 4-aminoquinoline decrease with the increase in temperature and concentration of organic-water solvent systems. The curve is a parabolic one. It is noted that the pKaMand pKaTvalues of this compound are higher than that quinoline and some of its amino derivatives. These results are discussed in terms of solvent characteristics, solvent basicity and stabilization of conjugate acid for base by hydrogen bonding interaction in hydro-organic solvent media. The values of dissociation constant are calculated by a computer program written in GW-BASIC. From p K. values Gibb's free energies are computed and discussed interms of solute solvent interactions.